Sağlık Bilimleri Fakültesi Birinci Sınıf Öğrencilerinin Bazı Bireysel Hijyen Uygulamalarına İlişkin Görüşleri - Ülker, Mediha (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
The research is made in compliance with descriptive research design to examine the views of first year students of graduate and undergraduate programs on various personal hygiene practices. The research population is composed of first year students of graduate and undergraduate programs of EMU Faculty of Health Sciences. Stratified sampling method has been used and the sample size has been identified as 417 students. The data is collected through the survey form under the name of “Views of First Year Students of Graduate and Undergraduate Programs on Various Personal Hygiene Practices”. Descriptive statistics and chi square significance test have been used for the statistical analysis of the data. The statistical significance level is accepted as p<0.05. While 86.8% of the students declared that one should take a bath every day during the summer season, 37.4% declared that one should take a bath every other day during the winter season. 96.9% of the students stressed that one should wash their hands after using the restroom, 76.3% after doing anything, 54.4% before starting anything for 2 and more than 2 minutes (61.2%). 62.8% of the students believe that fingernails should be oval and toenails should be square-shaped. 66.7% of the students think that one should brush their teeth twice a day, in the morning and in the evening, in circles (46.0%), for two minutes (41.7%). 26.6% of students stated that they have acquired information on personal hygiene from their families and 20.3% from the internet. It is determined that there is a significant difference between the frequency of taking a bath in summer and winter months and educational background of the mother (p<0.05). It is determined that there is a statistically significant difference between the views of students on the duration of hand washing and income status, department and educational background of the mother (p<0.05). It is determined that there is a statistically significant difference between the views of the students on duration of tooth brushing and gender and income status (p<0.05). Proposals have been made on training activities in respect to personal hygiene in accordance with the research results.

ÖZ: Araştırma, Sağlık Bilimleri Fakültesi birinci sınıf öğrencilerinin bazı bireysel hijyen uygulamalarına ilişkin görüşlerinin incelenmesi amacı ile tanımlayıcı araştırma tasarımına uygun olarak yapılmıştır. Araştırmanın evrenini, Doğu Akdeniz Üniversitesi Sağlık Bilimleri Fakültesi lisans ve ön lisans programları birinci sınıf öğrencileri oluşturmuştur. Araştırmada tabakalı örneklem yöntemi kullanılmıştır ve örneklem hacmi 417 öğrenci olarak hesaplanmıştır. Araştırmada veriler araştırmacı tarafından geliştirilen “Sağlık Bilimleri Fakültesi Lisans ve Ön Lisans Programları Birinci Sınıf Öğrencilerinin Bazı Bireysel Hijyen Uygulamalarına İlişkin Görüşleri Anket Formu” ile toplanmıştır. Verilerin istatistiksel analizinde tanımlayıcı istatistikler ile ki kare önemlilik testi kullanılmıştır. İstatistiksel önemlilik düzeyi p<0.05 olarak kabul edilmiştir. Öğrencilerin %86.8‟i yaz aylarında her gün, %37.4‟ü ise kış aylarında gün aşırı banyo yapılması gerektiğini bildirmişlerdir. Öğrencilerin %96.9‟u tuvaletten sonra, %76.3‟ü herhangi bir işi bitirdikten sonra, %54.4‟ü herhangi bir işe başlamadan önce ve 2 dk ve daha fazla süre (%61.2) ile ellerin yıkanması gerektiğini bildirmişlerdir. Öğrencilerin %62.8‟i el tırnaklarının oval, ayak tırnaklarının düz olacak şekilde kesilmesi ve %66.7‟sinin sabah ve akşam olmak üzere günde iki defa, dairevi hareketlerle (%46.0) ve iki dakika süreyle (%41.7) dişlerin fırçalanması gerektiği görüşündedirler. Öğrencilerin %26.6‟sı aileden, %20.3‟ü internetten bireysel hijyenle ilgili bilgi edindiklerini bildirmişlerdir. Yaz ve kış aylarında banyo yapma sıklığına ilişkin görüşleri ile anne eğitim durumu arasında istatistiksel olarak anlamlı fark olduğu saptanmıştır (p<0.05). Öğrencilerin el yıkama sürelerine ilişkin görüşleri ile gelir durumları, bölümleri ve anne eğitim durumları arasında istatistiksel olarak anlamlı fark olduğu saptanmıştır (p<0.05). Öğrencilerin diş fırçalama zamanına ilişkin görüşleri ile cinsiyet ve gelir durumu arasında istatistiksel olarak anlamlı fark olduğu saptanmıştır (p<0.05). Araştırmadan elde edilen sonuçlar doğrultusunda kişisel hijyene yönelik eğitim faaliyetlerine ilişkin öneriler sunulmuştur.
Hemşirelik Dalında Yüksek Lisans Tezidir. Tez (Yüksek Lisans)--Doğu Akdeniz Üniversitesi, Sağlık Bilimleri Fakültesi, Hemşirelik Bölümü, 2018. Tez Danışmanı: Prof. Dr. Refia Selma Görgülü.
Keywords: Hemşirelik; Kişisel Sağlık ve Hijyen; Bireysel hijyen; El yıkama; Üniversite öğrencileri; Personal hygiene; hand wash; university students